EVALUACIÓN FINANCIERA PARA LA CREACIÓN DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE CUADERNOS ECOLÓGICOS EN LA CIUDAD DE LOJA - Salazar Gonzaga, Mayra Alejandra (2019)
The thesis denominated, "FINANCIAL EVALUATION FOR THE CREATION OF A PRODUCING COMPANY AND COMMERCIALIZER OF ECOLOGICAL BOOKS IN THE CITY OF LOJA" has the purpose of presenting a proposal of creation of a company dedicated to the elaboration of ecological notebooks in an artisanal way, based on of waste from the banana plant, such as pinzote, which will have a medium size letter of 15 x 22 cm and 60 sheets, resulting in a good quality and cheaper notebook. It was based mainly on the market study to determine the unmet demand in the locality, for which the survey technique applied to the student community of the Loja canton was used. In addition, to determine the existing offer, the owners of the six stationery stores were interviewed with the largest inventories that are found in the locality, establishing an approximate average in the number of notebooks they acquire, for the other stationery shops and bazaars in the city. The technical study allowed to establish the appropriate place to build the microenterprise based on factors that condition its best location, such as the macro and micro location, establishing the distribution and design of the facilities. It also specified the production process that will entail developing the product, the technological components necessary for production and a functional organizational chart with which the company can start its productive activities. In